2018
DOI: 10.18203/2320-1770.ijrcog20185453
|View full text |Cite
|
Sign up to set email alerts
|

Camylofin dihydrochloride injection: a drug monograph review

Abstract: Camylofin dihydrochloride is an anti-spasmodic drug available in India and other Latin American and African countries, for the treatment of abdominal colic and for acceleration of labor. Although, the drug has been in use for over six decades, with multiple citations in academic text books of repute, treatment protocols, and multiple research publications, there is no consolidated published information on the pharmacology and clinical details of camylofin. This drug statement/monograph is an attempt to collate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…An Indian study on patients with intestinal, renal, and biliary colic demonstrated effective pain relief in more than 94% of study patients when treated with 25 mg camylofin. 13 These findings are consistent with those of an open-label, randomized, comparative study including 50 patients with abdominal spasmodic pain, in which an oral FDC of camylofin 25 mg and paracetamol 300 mg showed significantly higher reduction in VAS scores for pain compared with an FDC of dicyclomine 20 mg and paracetamol 500 mg, following 5 days of treatment, as well as significant improvement in tenderness, abdominal rigidity, and inflammation. 22 Additionally, in the present study, physicians' global assessment of pain further corroborated the effectiveness of the FDC in reducing pain, wherein approximately more than 85% of the patients demonstrated considerable improvement in pain intensity and majority of the patients felt better after 5 days of treatment.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…An Indian study on patients with intestinal, renal, and biliary colic demonstrated effective pain relief in more than 94% of study patients when treated with 25 mg camylofin. 13 These findings are consistent with those of an open-label, randomized, comparative study including 50 patients with abdominal spasmodic pain, in which an oral FDC of camylofin 25 mg and paracetamol 300 mg showed significantly higher reduction in VAS scores for pain compared with an FDC of dicyclomine 20 mg and paracetamol 500 mg, following 5 days of treatment, as well as significant improvement in tenderness, abdominal rigidity, and inflammation. 22 Additionally, in the present study, physicians' global assessment of pain further corroborated the effectiveness of the FDC in reducing pain, wherein approximately more than 85% of the patients demonstrated considerable improvement in pain intensity and majority of the patients felt better after 5 days of treatment.…”
Section: Discussionsupporting
confidence: 87%
“…12 It is a highly effective antispasmodic owing to its direct papaverine like spasmolytic action on smooth muscles and a mild atropine like anticholinergic action. 13 Via its anticholinergic activity, camylofin blocks muscarinic type-3 receptors on smooth muscle cells of the colon and reduces their motility. 14 As its anticholinergic effects are less pronounced, camylofin has a good safety profile with palpitations, dilatation of pupils, and dryness of mouth reported as frequent adverse events (AEs).…”
Section: Introductionmentioning
confidence: 99%
“…1 The major factors responsible for pain in visceral organs are abnormal contraction and distension of the hollow structures, traction or compression of ligaments, stretching of the capsule of solid visceral organs, ischemia of visceral musculature, and accommodation of algogenic substances. 2 In addition, pain could result from muscle contraction around partial or complete blockage in any of the hollow organs.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] Since more than five decades, camylofin dihydrochloride, a potent and safe antispasmodic, in a dose of 25 mg administered intravenously or intramuscularly, has been used to treat symptoms related to biliary, renal, and ureteric colic pain, and menstrual pain. 2 A study conducted in the Indian population showed a substantial increase in antispasmodic effect of camylofin dihydrochloride when used intravenously along with nonsteroidal anti-inflammatory drugs (NSAIDs). 15 The other therapeutic agent in the FDC is nimesulide, which is an NSAID with relatively selective inhibitory potential toward cyclooxygenase-2 (COX-2) and possesses analgesic and antipyretic properties.…”
Section: Introductionmentioning
confidence: 99%
“…anticholinergic effect, which is elicited by inhibiting the binding of acetylcholine with muscarinic receptors. 12 Non-steroidal anti-inflammatory drugs (NSAIDs), which act by blocking prostaglandin production, have been widely used to manage painful cramps in dysmenorrhea. 13 Mefenamic acid is an NSAID with anti-inflammatory, antipyretic, and analgesic activities.…”
mentioning
confidence: 99%